Pengaruh Penyuluhan Nutrisi Pemberian Asam Folat Alami terhadap Peningkatan Hemoglobin pada Ibu Hamil - Nofita Zuhriana; Laily Prima Monica (STIKes Patria Husada Blitar, 2015)
Folat acid is needed in forming 1/3 corpuscle. It causes pregnant woman who suffers from lacking of folat acid commonly followed by anemia. Folat acid is a vitamine that more needed by pregnant woman. The purpose of this research is to find out if there is effect of natural folat acid counseling to the rising of hemoglobin in trimester I and II pregnant women. The research design of this study is pre-experimental that uses one shoot case approach. The population of this research are 20 responden of trimester I and II pregnant women in BPM Sumidjah of Slorok, using total sampling technique. The instrument of this research is SOP sheet, the observation sheet of the rising of hemoglobin after the counseling. After that, it is analyzed using wilcoxon.The result is served in a table from. The rising of hemoglobin is about 70% in which 25% of pregnant women medium anemia has 95% rising of with light category.There was a significant increase in hemoglobin levels in pregnant women. The effect of the nutrition of natural folat acid the rising of hemoglobin that can prevent the risk of maternal and fetal death due to anemia.